2021
DOI: 10.1021/acs.jpclett.1c01083
|View full text |Cite
|
Sign up to set email alerts
|

Water Microdroplets Allow Spontaneously Abiotic Production of Peptides

Abstract: The chemistry of abiotic synthesis of peptides in the context of their prebiotic origins is a continuing challenge that arises from thermodynamic and kinetic constraints in aqueous media. Here we reported a strategy of microdroplets’ mass spectrometry for peptide bonds formed from pure amino acids or a mixture in the presence of phosphoric acids in aqueous microdroplets. In contrast to bulk experiments, the condensation reactions proceed spontaneously under ambient conditions. The microdroplet gave a negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…Of particular interest is the observation that the air–water interface of monolayers and thin films ( 28 31 ), inverted micelle aerosols ( 12 ), Leidenfrost droplets ( 32 36 ), and charged or neutral microdroplets ( 37 46 ) all reveal vastly different chemical kinetics compared to bulk, with rate constants increased by up to six orders of magnitude ( 47 , 48 ). This interfacial acceleration phenomenon has been reported for prebiotically relevant reactions including condensation ( 12 , 21 , 29 , 49 53 ), redox ( 54 , 55 ), nucleophilic addition ( 41 , 43 ), and ultraviolet-initiated photopolymerization reactions ( 56 ). The observed rate constant is associated with high surface-to-volume ratios, and it has been attributed to the partial solvation of species at the interface ( 47 , 48 , 57 , 58 ) along with the high electric field at the air–solvent interface ( 55 , 59 61 ).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Of particular interest is the observation that the air–water interface of monolayers and thin films ( 28 31 ), inverted micelle aerosols ( 12 ), Leidenfrost droplets ( 32 36 ), and charged or neutral microdroplets ( 37 46 ) all reveal vastly different chemical kinetics compared to bulk, with rate constants increased by up to six orders of magnitude ( 47 , 48 ). This interfacial acceleration phenomenon has been reported for prebiotically relevant reactions including condensation ( 12 , 21 , 29 , 49 53 ), redox ( 54 , 55 ), nucleophilic addition ( 41 , 43 ), and ultraviolet-initiated photopolymerization reactions ( 56 ). The observed rate constant is associated with high surface-to-volume ratios, and it has been attributed to the partial solvation of species at the interface ( 47 , 48 , 57 , 58 ) along with the high electric field at the air–solvent interface ( 55 , 59 61 ).…”
supporting
confidence: 56%
“…Multiple studies have described dehydration reactions occurring at the air–water interface of aqueous microdroplets ( 25 , 29 , 49 , 51 , 52 , 70 ). Others have reported that the free energy of some endothermic reactions in bulk solution are negative when reagents are at the surface of the droplet, leading to spontaneous conversion ( 49 , 51 , 71 ).…”
mentioning
confidence: 99%
“…Given the importance of catalysts for prebiotic chemistry, minerals, such as clays were probably the most efficient partners of the primitive game of life (Brack, 2013;Hansma, 2022;Kloprogge and Hartman 2022) but other minerals with reactive surfaces were present on the early Earth, such as spinels, could have been equally useful (Iqubal et al, 2016). The use of microdroplets represents also an interesting avenue for the synthesis of both peptides and nucleotides (e.g., Wang et al, 2021).…”
Section: Which Time Scale For the Emergence Of Life?mentioning
confidence: 99%
“…The atmospheric aerosols have been reported as prebiotic chemical reactors. , In contrast to bulk aqueous solution, microdroplets have been shown to mediate various reactions at or near the water surface with an acceleration of 10 3 - to 10 6 -fold, including addition, elimination, , redox reaction,s , and the ultrafast enzymatic digestion of proteins . We have successfully demonstrated the condensation of amino acids to peptides in microdroplets . Recent studies have shown that microdroplets give a negative Gibbs free energy change and facilitate the formation of ribonucleosides by simply mixing ribose, phosphoric acid, nucleobases, and small amounts of magnesium ion. , However, the knowledge of this key phosphorylation of ribonucleotides in microdroplets has not been investigated and remains limited and incomplete.…”
mentioning
confidence: 94%
“…31 We have successfully demonstrated the condensation of amino acids to peptides in microdroplets. 32 amounts of magnesium ion. 4,14 However, the knowledge of this key phosphorylation of ribonucleotides in microdroplets has not been investigated and remains limited and incomplete.…”
mentioning
confidence: 99%